Keberkesanan Penggunaan Grafik Berkomputer Sebagai Alat Bahan Bantu Mengajar Dalam Kalangan Pelajar Reka Bentuk Dan Teknologi (Sains Humanika, 2018)
This study aims to identify the effectiveness of computerized graphics usage as a teaching tool among students in a secondary school. A total of 30 students were chosen as respondents for this study. The research instruments used were questionnaire, pre and post test. A set of questionnaire comprising two parts, part A (respondents’ demographics) and part B (questions related to research questions) were used. The data obtained were processed and analyzed using Statictical Package for Social Science version 20 (SPSS). While data analysis used was descriptive statistical values such as frequency, percentage, standard deviation, mean and T-test. In addition, students were divided into two groups, namely traditional group and Graphic learning group. The findings of the study showed that computerized learning graphs could  affect and increase interest and motivation. Furthermore, through pre and post tests, there was  a difference in the achievement of Form 1 students in Design and Technology (RBT) subject using computerized graphics with the use of traditional learning methods
Keywords: Graphics; computer; teaching aids; design and technology